Trademark Influence and Brand Experience on Consumer's Loyalty to Fast Fashion Brands - Valenzuela Quintero, Ana Rocío; Bellon Álvarez, Luis Alberto (Mercados y Negocios, 2023)
This work investigates the relationship between Brand love and Brand Experience with Brand Loyalty in fast fashion consumers in the ZMG. A quantitative instrument was built from whose answers it is intended to know if there is a positive relationship between the concepts of Love and Brand Experience and Brand Loyalty. From the results obtained, it sought to know the characteristics of the market, as well as the purchasing behavior and which of the brands studied is a favorite. The ANOVA was used to check whether the hypotheses were approved or rejected and to know the most critical consumer dimensions when developing loyalty to a fast fashion brand. The results reveal a positive relationship between the Brand Loyalty and Brand Experience and Brand Love scales. Therefore, the 2 Hypotheses presented for this study were accepted.